Organizational Citizenship Behavior Level Scale For Administrative Employees At Tishreen University A Comparative Study Between The Faculty Of Economics And The Faculty Of Arts And Humanities - هبرة لينا; نهاد نادر; سامر قاسم (Latakia University Journal - Economic and Legal Sciences Series, 2025)
The research aimed to determine the level of organizational citizenship behavior with its dimensions (altruism, civility, sportsmanship, conscientiousness, and civilized behavior) among administrative workers in the Faculties of Economics and Arts at Tishreen University, and to make a comparison among them at the level of these dimensions. The research adopted the descriptive approach, and the research community included all administrative workers in the Faculties of Economics and Arts and Humanities at Tishreen University, who numbered (260) male and female workers, including (133) male and female workers in the Faculty of Economics, and (127) male and female workers in the Faculty of Arts and Humanities. The researcher adopted the comprehensive inventory method, and the questionnaire (research tool) was distributed to all administrative workers, and (233) complete questionnaires were retrieved and suitable for statistical analysis, including (121) questionnaires from the College of Economics, and (112) questionnaires from the College of Arts, and a percentage Response amounted to .(89.62%) The research results showed that the level of organizational citizenship behavior (OCB) among administrative staff in the Faculties of Economics and Arts at Tishreen University was high. Additionally, there was no statistically significant difference between the means of the responses of administrative staff in the two faculties regarding the level of OCB in general and in terms of the sub-dimensions (altruism, courtesy, sportsmanship, conscientiousness, and civic behavior). The research presented a set of recommendations, the most important of which were: Encourage open communication and dialogue between management and employees. Create a work environment that values and rewards OCB. Focus on teamwork and cooperation between different departments. Provide opportunities for participation in decision-making. Spread a culture of appreciation and recognition of efforts.